Numerical Simulation of Solitary Waves by SPH Method and Parametric Studies on the Effect of Wave Height to Water Depth Ratio - Ghadimi, Parviz; Abtahi, Shahryar; Dashtimanesh, Abbas (International Journal of Engineering and Technology, 2012)
Numerical simulation of fluid flow phenomena, including complicated free surface deformation, has been a main research interest for many authors. In this context, using mesh based methods has been a common choice in the past decades. However, in the recent years, Smoothed Particle Hydrodynamics (SPH) as a Lagrangian meshless method has been utilized in many of applications. In the present article, a two dimensional solitary wave on a beach is generated and the effect of various wave heights to water depth ratios on solitary wave generation are studied. Furthermore, condition in which wave breaking occurs is also considered. Finally, the results of SPH simulations are compared against the available results in the literature and it is shown that Solitary wave profile simulated by SPH is in good agreement with experimental data.